A systematic review of collective tactical behaviours in football using positional data - Low, B.; Coutinho, D.; Goncalves, B.; Rein, R.; Memmert, D.; Sampaio , J. (Sports Medicine, 2020)
Background: Performance analysis research in association football has recently cusped a paradigmatic shift in the way tactical behaviours are studied. Based on insights from system complexity research, a growing number of studies now analyse tactical behaviours in football based on the collective movements of team players. Objective: The aim of this systematic review is to provide a summary of empirical research on collective tactical behaviours in football, with a particular focus on organising the methods used and their key findings. Methods: A systematic search of relevant English-language articles was performed on one database (Web of Science Core Collection) and one search engine (PubMed), based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines. The keywords `football` and `soccer` were each paired with all possible combinations of the following keywords: `collective movement behaviour`, `collective behaviour`, `tactical behaviour`, `interpersonal coordination`, `space`, `Voronoi`, `synchronisation`, `tactical analysis`, `constraints`, `ecological dynamics`, and `dynamic positioning`. Empirical studies that were related to tactical analyses of footballers` positional data were sought for inclusion and analysis. Results: Full-text articles of 77 studies were reviewed. A total of 27 tactical variables were identified, which were subsequently organised into 6 categories. In addition to conventional methods of linear analysis, 11 methods of nonlinear analysis were also used, which can be organised into measures of predictability (4 methods) and synchronisation (7 methods). The key findings of the reviewed studies were organised into two themes: levels of analysis, and levels of expertise. Conclusions: Some trends in key findings revealed the following collective behaviours as possible indicators of better tactical expertise: higher movement regularity; wider dispersion in youth players and shorter readjustment delay between teammates and opponents. Characteristic behaviours were also observed as an effect of playing position, numerical inequality, and task constraints. Future research should focus on contextualising positional data, incorporating the needs of coaching staff, to better bridge the research-practice gap.